Clinical Practice Guidelines in Traditional Chinese Medicine Rehabilitation—Cervical Spondylosis (Xiangbi) - Working Group on Setting up Standardization Guidelines of Cervical Spondylosis (Xiangbi) in Traditional Chinese Medicine Rehabilitation; Wei ZHANG; Jinxiang LI; Bidan LOU; Yong YE; Wenying SHI; Hongliang LI; Zhaoan YU; Kangsheng LONG; Ran PENG; Jing TANG; Yanzhen XIONG (康复学报)
Cervical spondylosis is a disease in which degenerative changes of the cervical intervertebral disc and its secondary pathological changes involve a series of clinical manifestations. It is one of the common clinical diseases and the frequently-occurring diseases. Traditional Chinese medicine (TCM) rehabilitation is one of the effective ways to improve its clinical symptoms and prevent recurrence. In order to standardize the operating of TCM rehabilitation for cervical spondylosis and guide the clinical practice, the expert group composed the Clinical Practice Guidelines in Traditional Chinese Medicine Rehabilitation-Cervical Spondylosis (Xiangbi). Based on evidence-based medicine concepts and methods, with expert consensus and argumentation, and clinical evaluation and other evidences, in accordance with the clinical diagnosis and treatment guidelines and reporting rules, this guide is suitable for various types of rehabilitation institutions in China, and for other TCM hospitals or for rehabilitation departments of general hospitals etc. The guideline is of importance for applicability and effectiveness. It will provide standardized diagnosis and treatment procedures for TCM rehabilitation treatment, and provide reliable evidence for the practice of cervical spondylosis clinical decision-making.